The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/03630242.2014.932889
|View full text |Cite
|
Sign up to set email alerts
|

Reentry Challenges Facing Women with Mental Health Problems

Abstract: Women entering the correctional system represent a population at high risk for mental health and the body of research on the mental health needs of women offenders is growing. These mental health problems pose challenges for women at every stage of the criminal justice process, from arrest to incarceration to community reentry and reintegration. In this article, we examined mental health status among a sample of 142 women leaving confinement and the role that mental health problems played in shaping their reen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…4 Women with incarceration histories bear a disproportional burden of infectious and chronic disease when compared to the general population, in addition to histories of substance use, mental health problems, and personal trauma. 1,5-9 Yet, despite these health problems, previous studies have shown that few receive care while detained, 10,11 and up to 48% do not seek healthcare services after release from jail. 11,12 According to Lee et al, 12,13 women do not seek health services after release from jail, primarily because of financial barriers (in particular lack of health insurance) and the number of other concerns demanding their attention after incarceration.…”
mentioning
confidence: 99%
“…4 Women with incarceration histories bear a disproportional burden of infectious and chronic disease when compared to the general population, in addition to histories of substance use, mental health problems, and personal trauma. 1,5-9 Yet, despite these health problems, previous studies have shown that few receive care while detained, 10,11 and up to 48% do not seek healthcare services after release from jail. 11,12 According to Lee et al, 12,13 women do not seek health services after release from jail, primarily because of financial barriers (in particular lack of health insurance) and the number of other concerns demanding their attention after incarceration.…”
mentioning
confidence: 99%
“…To be considered comprehensive, such services should also include managing mental and physical health problems, given the prevalence of those within the population. Prior research has shown that that incarcerated women's healthcare needs related to physical and mental health only added to the burden of successful reentry (Sered & Norton-Hawk, 2008;Visher & Bakken, 2014). Attention to health promotion and self-care is a necessary component of the healthcare continuum, and this time of transition may be an ideal time for intervention by nurses.…”
Section: ▪ Backgroundmentioning
confidence: 99%
“…T he time of transition after incarceration is widely regarded as tenuous and stressful (Flores & Pellico, 2011;Solomon, Osborne, LoBuglio, Mellow, & Mukamal, 2008;Visher & Bakken, 2014). Familial obligations, requirements for compliance with criminal justice supervision, finding employment, and managing addiction are only a few of the many obstacles faced by people recently released from jail or prison.…”
mentioning
confidence: 99%
“…Third, the prevalence of mental illness could not be determined; only a measure of mental health treatment was available for inclusion in this study per IRB requirements. Although this proxy is not an optimal measure, the use of prior mental health treatment, as well as mental health self-report, has been employed in reentry research (e.g., Freundenberg, Daniels, Crum, Perkins, & Ritchie, 2005;Mallik-Kane & Visher, 2008;Visher & Bakken, 2014). Finally, the unanticipated result related to marriage could not be further explored for two reasons: 1) the number of married participants in the sample was too small to determine whether the finding was merely an artifact of the data and 2) information about the marital relationship (e.g., marriage quality, strength of bonds, marital strife) did not exist in the data.…”
Section: Limitationsmentioning
confidence: 99%